Nonlinear Impulsive Integrodifferential Equations with Nonlocal Conditions in Banach Spaces - et al., Venkatesan (International Journal of Advanced Science and Technology, 2019)
We study the existence and uniqueness of mild and classical solutions for a  impulsive integro-differential systems with nonlocal conditionsBy combining and extending some earlier work on equations with nonlocal condition and equations with impulsive condition.  Here,  is the generator of a strongly continuous semigroup in a Banach space (BS),  Here   .  is a continuous nonlocal condition, and  constitutes in impulsive condition.  New results are obtained.